Attitudes towards STEM education: nonlinear effects of teachers’ readiness and the crucial role of affective conditions - Vaiopoulou, Julie; Papagiannopoulou, Theano; Stamovlasis, Dimitrios (Frontiers in Education, 2024)
Teacher attitudes (Att) towards STEM-Science, Technology, Engineering, and Mathematicseducation is decisive for its successful integration into contemporary curricula. On the other hand, teachers' readiness for STEM influences their attitudes and controls their behavior in everyday practice. In this work, the four dimensions of readiness for STEM, i.e., affective conditions (Affe), cognitive preparedness (Cogn), self-efficacy (SEff), and STEM commitment (Com), measured via the TRi-STEM scale, were tested as predictors of attitudes using nonlinear models. Data were taken from teachers (N= 494) who completed the TRi-STEM questionnaire and the Attitudes Towards STEM scale for measuring attitudes. Catastrophe theory was applied, and three cusp models, superior to the linear and logistic counterparts, were proposed predicting Attitudes (Att) as a function of combinations of Cogn, SEff, Com, and Affe. Specifically, the three models are: Cusp 1 with (Cogn -Affe) as asymmetry and (Cogn + Affe) as bifurcation factors; Cusp 2 with (Com -Affe) as asymmetry and (Com + Affe) as bifurcation factors, and Cusp 3 with (SEff -Affe) as asymmetry and (SEff + Affe) as bifurcation factors. The findings showed that affective conditions involved in a dynamical interplay with other independent variables could lead to sudden and abrupt changes in Att. The empirical evidence for nonlinear effects in teacher attitudes (Att) towards STEM informs theory development and practice by supporting the complexity and dynamical system framework as a more realistic premise to describe and interpret potentially occurring phenomena of teachers' behavior in the context of STEM education.